Introduction - Jean Franco (Studies in 20th & 21st Century Literature, 1990)
Introduction to the special issue.
Keywords: Latin American literature; dark; mode; women; subaltern classes; indigenous; postmodernism; authoritarian modernization; progress; national emancipatio